Amphiphilic Biopolyester‐Carbon Nanotube Anode Enhances Electrochemical Activities of Microbial Fuel Cell - Yusuf, Hindatu; Annuar, Mohamad Suffian Mohamad; Ramesh, Subramaniam; Gumel, Ahmad Mohammed (Wiley, 2019)
Hydrophobic bacterial polyhydroxyalkanoates were rendered amphiphilic by grafting with poly(ethylene glycol) methacrylate, followed by compositing with carbon nanotubes. The polymer graft composite as an anode material encouraged superior biofilm surface growth; thus enhancing electrochemical activities in microbial fuel cells and resulting in higher current and power densities. The internal resistance of the cell was greatly reduced due to improved electron transfer from the biofilm to the anode.